1) 3+2+15=20
2) 3/4= 27/36 1/9=4/36
3) 27/36+4/36=31/36
4) 26/27=936/972 31/36= 637/972
5) 936/972 + 637/972= 1573/972= 1 601/972
Answer:
I believe the answer is y-axis
Step-by-step explanation:
Answer:
first we find the common difference.....do this by subtracting the first term from the second term. (9 - 3 = 6)...so basically, ur adding 6 to every number to find the next number.
we will be using 2 formulas....first, we need to find the 34th term (because we need this term for the sum formula)
an = a1 + (n-1) * d
n = the term we want to find = 34
a1 = first term = 3
d = common difference = 6
now we sub
a34 = 3 + (34-1) * 6
a34 = 3 + (33 * 6)
a34 = 3 + 198
a34 = 201
now we use the sum formula
Sn = (n (a1 + an)) / 2
S34 = (34(3 + 201))/2
s34 = (34(204)) / 2
s34 = 6936/2
s34 = 3468 <=== the sum of the first 34 terms:
Answer:
13. 5^7
14. 7^1000
15. 16^10000
25 x 10 x 10 x 10 x 10 x 10 x 10
Step-by-step explanation: